Occipitoatlantoaxial Malformation in a Dog Treated with a Custom-Made Implant - Rotter, Carina; Rusbridge, Clare; Fitzpatrick, Noel (VCOT Open, 2020)
Background Occipitoatlantoaxial malformation (OAAM) is reported rarely in dogs and few treatment options are described. The congenital condition is thought to be associated with a proatlas re-segmentation failure resulting in malformation and malalignment of the craniovertebral junction which can result in C1 to 5 myelopathic signs.Methods Customized three-dimensional printed locking plate with trajectory screw implantation points for the stabilization of the atlantoaxial joint in a dog with OAAM. The dog was evaluated at time points 0, 2, 6 and 9 months to determine clinical outcome, degree of fusion, implant positioning and subsidence.Results New bone formation was noted 9 months after surgery, but complete fusion remained absent, although no implant failure occurred. Clinically, the dog made a good recovery and was able to exercise normally 9 months after surgery. The only residual deficit was a subtle left-sided cervical torticollis.Clinical Significance This report illustrates a management option and outcome of a dog treated with OAAM. Collaboration between clinicians and engineers provides a new dimension of care for patients with vertebral malformations.
Keywords: three-dimensional printed locking plate; patient-specific implant design; cervical vertebral malformation; canine occipitoatlantoaxial malformation